2008
DOI: 10.1111/j.1540-8167.2008.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Fibrillation with Prominent Early Repolarization Associated with a Rare Variant of KCNJ8/KATP Channel

Abstract: This young female (14 years) was resuscitated in 2001 following an episode of sudden death due to VF. All examinations including coronary angiogram with ergonovine injection, MRI, and flecainide or isoproterenol infusion were normal. The patient had multiple (>100) recurrences of VF unresponsive to beta-blockers, lidocaine/mexiletine, verapamil, and amiodarone. Recurrences of VF were associated with massive accentuation of the early repolarization pattern at times mimicking acute myocardial ischemia. Coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(178 citation statements)
references
References 29 publications
7
165
1
5
Order By: Relevance
“…One limitation of our study is that, even though our sample size (162 patients) was larger than previous Kir6.1 gene mutation studies (19)(20)(21), our study population may be too small to confirm an association of the I37I polymorphism and BP response to iptakalim due to the low prevalence of this polymorphism in our study. Therefore a larger sample is needed to more accurately determine whether or not the I37I polymorphism is associated with BP response to iptakalim treatment.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…One limitation of our study is that, even though our sample size (162 patients) was larger than previous Kir6.1 gene mutation studies (19)(20)(21), our study population may be too small to confirm an association of the I37I polymorphism and BP response to iptakalim due to the low prevalence of this polymorphism in our study. Therefore a larger sample is needed to more accurately determine whether or not the I37I polymorphism is associated with BP response to iptakalim treatment.…”
Section: Discussionmentioning
confidence: 52%
“…A complete mutational analysis of the Kir6.1 gene was performed in a series of 18 Italian patients with impaired coronary vasomotility, and no mutations were detected in the sample analyzed, thus suggesting that Kir6.1 gene aberrations are not a common cause of abnormal coronary vasomotility in Italians (20). A rare missense variant in exon 3 of the Kir6.1 gene was found to be associated with ventricular fibrillation with prominent early repolarization (21). The mutational analysis of the Kir6.1 gene among various ethnic groups showed that it may be so important that no mutations or polymorphisms that alter the primary structure of Kir6.1 are allowed.…”
Section: Discussionmentioning
confidence: 99%
“…The KCNJ8-S422L variant mutation was first described in a young female with ER pattern and frequent episodes of VF. 48 Subsequently, loss of function mutations was found in the SCN5A gene and L-type calcium channel genes (LTCC, CACNA1C, CACNB2, CACNA2D1) in patients with idiopathic VF and ER. 49,50 Moreover, genetic variants have been identified in the ABCC9 gene, encoding the ATP-binding cassette transporters of ATP-sensitive potassium channels.…”
Section: Ecg Is Characterised By a Coved-type St-segment Elevation ≥2mentioning
confidence: 99%
“…Since then there have been several studies reporting genetic associations with IVF, with KCND3, KCNJ8, CALM1, RYR2, and SCN3B being implicated. These are, however, mostly case series of isolated findings with a number of limitations (30)(31)(32)(33)(34)(35)(36)(37). These include: variability in the definition of IVF and therefore the possibility of other incompletely penetrant conditions; the absence of segregation in large families to strengthen association; and a reliance on in vitro basic electrophysiological data that may be open to interpretation.…”
Section: Genetic Testing In Idiopathic Vfmentioning
confidence: 99%